PENGARUH KEMANDIRIAN BELAJAR, PERGAULAN TEMAN SEBAYA, TINGKAT PENDIDIKAN ORANG TUA, SARANA BELAJAR, MELALUI MINAT BELAJAR SEBAGAI VARIABEL NTERVENING TERHADAP PRESTASI BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN IPS DI MTsN 4 PASAMAN - Berti, Dinda Oktavia; Verawati, Rika; Selvia, Nisha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze: 1) the influence of independent learning on interest in learning. 2) the influence of peer interactions on interest in learning. 3) the influence of parental education level on interest in learning. 4) the influence of learning facilities on interest in learning. 5) the influence of learning independence on learning achievement. 6) the influence of peer interactions on learning achievement. 7) parental education level on learning achievement. 8) the influence of learning facilities on learning achievement. 9) the influence of learning interest on learning achievement. The type of research used in this research is associative descriptive research. The population of this research was all 122 students in class VIII IPS MTsN 4 Pasaman. The sampling technique was proportional random with a sample size of 122 students. The data analysis techniques used are descriptive analysis techniques and path analysis, with the help of the SPSS version 16.0 program. The results of the research show that 1) learning independence has a positive and significant effect on interest in learning, with a path coefficient value of 0.242 and a t-count value of 2.833 > ttable 1.658. 2) peer interaction has a positive and significant effect on interest in learning, with a path coefficient value of 0.216 and a t-count value of 2.518 > ttable 1.658. 3) the level of parental education has a negative and significant effect on interest in learning. The path coefficient value is -0.221 and the t-count value is -2.694 > ttable 1.658. 4) learning facilities have a negative and significant effect on interest in learning, the path coefficient value is -0.216 and the tcount value is -2.635>ttable 1.658. 5) learning independence has a positive and significant effect on learning achievement, with a path coefficient value of 0.201 and a t-count value of 2.374 > ttable 1.658. 6) peer interaction has a negative and significant effect on learning achievement, with a path coefficient value of -0.447 and a t-count value of -5.296 > ttable 1.658. . 7) Parental education level has a positive and significant effect on learning achievement, with a path coefficient value of 0.306 and a tcount value of 3.780 > ttable 1.658. 8) learning facilities have a positive and significant effect on learning achievement, the path coefficient value is 0.246 and the tcount value is 3.041 > ttable 1.658. 9) interest in learning has a positive and significant effect on learning achievement, with a path coefficient value of 0.287 and a tcount value of 3.241 > ttable 1.658.